P1387IRON CITRATE BLOCKS THE PROGRESSION OF CALCIUM DEPOSITION BY REVERTING APOPTOSIS AND AUTOPHAGY IN VSMCS. (6th June 2020) - Ciceri, Paola; Falleni, Monica; Tosi, Delfina; Martinelli, Carla; Cozzolino, Mario Gennaro
Abstract: Background and Aims: Cardiovascular disease is the first cause of mortality in chronic kidney disease (CKD) induced by vascular calcification. Since, in advanced CKD, iron based phosphate binders have been proposed to treat hyperphosphatemia, we studied, in high-phosphate (Pi) calcified VSMC, the effect of iron citrate (iron) on the progression of calcium deposition. Method: We treated VSMCs with 5 mM Pi and iron citrate to evaluate Ca deposition by Alizarin Red destaining, DNA fragmentation by ELISA, gene expression by RT-PCR and protein expression by Western blot. Results: High-Pi calcification was blocked when iron was added from day 7 to 15 (1.30±0.03 vs 0.61±0.02; OD/mg protein; day 15; Pi vs Pi+Fe, p<0.01). Since iron added prophylactically prevented apoptosis and potentiated autophagy we studied the role of these two processes in the therapeutic protocol. Adding iron from day 7 to day 11 decreased apoptotic cell number (17.3±2.6 vs 11.6±1.6; Annexin V; % positive cells; day 11; Pi vs Pi+Fe; p<0.05, figure). To confirm the effect of iron on apoptosis, we demonstrated its action in blocking the H2 O2 -induced increase in calcification when added from day 7 to day 14 (1.37±0.03 vs. 0.96±0.05; H2 O2 +Pi day 7-14 vs Fe+H2 O2 +Pi day 7-14; day 14; OD/mg protein; p<0.01). We then investigated the mechanism of the anti-apoptotic effect by studying the pro-survival axis GAS6/AXL, finding that iron treatment from day 9 to day 14 counteracted the protein down-regulation, and induced their de-novo synthesis. Supporting the effect of therapeutic added iron on apoptosis we found a decrease in apoptotic nuclei both in VSMCs and aortic rings after iron treatment from day 7 to 15 (3.8±0.2 vs 2.3±0.3 and 4.0±0.3 vs 2.2±0.2; apoptotic nuclei; arbitrary score; day 15; Pi vs Pi+Fe; VSMCs and aortic rings; p<0.05). Moreover, iron added from day 9 to day 15 potentiated autophagic flux and increased the number of autophagosomes with damaged mitochondria. Conclusion: Iron exerts an anti-apoptotic and pro-autophagic effect on established calcified VSMC when simil-osteoblastic transformation was already occurred.